MANAJEMEN PEMBELAJARAN BERBASIS MEDIA AUDIO VISUAL DALAM MENINGKATKAN MINAT BELAJAR IPA SISWA Kelas VI DI SEKOLAH DASAR - Ate Jamaludin Mubarok; Ani Kania; Dinny Mardiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the management of audio-visual media-based learning in enhancing the interest in learning Science for sixth-grade students at SDN Margasari, Campaka, Cianjur Regency. The research focuses on how audio-visual media is planned, implemented, and evaluated to achieve an increase in learning interest. This study employs a case study approach with a qualitative method. Data was collected through participatory observation, in-depth interviews with the school principal, teachers, and students, as well as documentation studies.The results show that the management of audio-visual media-based learning at SDN Margasari has been well-implemented, covering the planning stage, which involves selecting and adapting material to the media; the implementation stage, which includes the use of projectors, sound, and engaging visuals; and the evaluation of media usage effectiveness. The use of audio-visual media proved capable of creating a more interactive and enjoyable learning atmosphere, thus having a positive impact on the students' interest in learning Science. Students became more enthusiastic in following lessons, found it easier to understand abstract concepts, and showed a greater desire to explore Science material. Nevertheless, there were some challenges related to the availability and maintenance of media facilities, as well as the need for continuous training for teachers. This research recommends the importance of continuous support from the school and education department for the optimal use of audio-visual media in learning.